Multi-layer health-aware economic predictive control of a pasteurization pilot plant - Karimi Pour, Fatemeh; Puig, Vicenç; Ocampo-Martinez, Carlos (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes two different health-aware economic predictive control strategies that aim at minimizing the damage of components in a pasteurization plant. The damage is assessed with a rainflow-counting algorithm that allows estimating the components` fatigue. By using the results obtained from this algorithm, a simplified model that characterizes the health of the system is developed and integrated into the predictive controller. The overall control objective is modified by adding an extra criterion that takes into account the accumulated damage. The first strategy is a single-layer predictive controller with an integral action to eliminate the steady-state error that appears when adding the extra criterion.
Keywords: model predictive control; two-layers control scheme; fatigue; economic optimization; health-aware controller